Pengaruh Brand Image dan Brand Love Terhadap Repurchase Intention (Studi Kasus pada Konsumen Produk Gucci di Surabaya) - Miko Rakatama Adhi Winarto; Widyastuti Widyastuti (Inspirasi Nusantara, 2021)
Fashion is an inseparable part of the appearance and lifestyle that tends to be branded goods or luxury goods. Fashion manufacturers not only produce products with good quality but must be able to present a product with a good brand image in the eyes of consumers. Apart from the image of a brand, what needs to be considered next is love for the brand. The purpose of this study was to determine the effect of brand image and brand love on consumer repurchase intention of Gucci products in Surabaya. This research is included in quantitative research. Sampling using purposive sampling technique. The number of samples in this study were 75 respondents. The data collection technique used a questionnaire and the data analysis technique used multiple linear regression analysis with the help of SPSS 25.0 software. The results of the research show that brand image affects the repurchase intention of Gucci products in Surabaya and brand love affects the repurchase intention of Gucci products in Surabaya.